2000
DOI: 10.1182/blood.v96.13.4246.h8004246_4246_4253
|View full text |Cite
|
Sign up to set email alerts
|

Fyn and Lyn phosphorylate the Fc receptor γ chain downstream of glycoprotein VI in murine platelets, and Lyn regulates a novel feedback pathway

Abstract: Activation of platelets by collagen is mediated by the complex glycoprotein VI (GPVI)/Fc receptor γ (FcRγ chain). In the current study, the role of 2 Src family kinases, Fyn and Lyn, in GPVI signaling has been examined using murine platelets deficient in one or both kinases. In the fyn−/−platelets, tyrosine phosphorylation of FcRγ chain, phopholipase C (PLC) activity, aggregation, and secretion are reduced, though the time of onset of response is unchanged. In the lyn−/−platelets, there is a delay of up to 30 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
1
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 25 publications
2
23
1
1
Order By: Relevance
“…Quercetin was found to inhibit tyrosine phosphorylation of the FcR g-chain and therefore appears to have an inhibitory effect at the top of the collagen-stimulated activation pathway. Tyrosine phosphorylation of the FcR g-chain is thought to involve the activity of two Src-family kinases, namely Fyn and Lyn [26,27]. We have also shown that quercetin is able to inhibit the kinase activity of Fyn and Lyn in a concentration-dependent manner, both via GPVI (in whole cells) and directly.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Quercetin was found to inhibit tyrosine phosphorylation of the FcR g-chain and therefore appears to have an inhibitory effect at the top of the collagen-stimulated activation pathway. Tyrosine phosphorylation of the FcR g-chain is thought to involve the activity of two Src-family kinases, namely Fyn and Lyn [26,27]. We have also shown that quercetin is able to inhibit the kinase activity of Fyn and Lyn in a concentration-dependent manner, both via GPVI (in whole cells) and directly.…”
Section: Discussionmentioning
confidence: 76%
“…The tyrosine phosphorylation of the FcR g-chain following collagen binding to GPVI is mediated by the Src-family kinases Fyn and Lyn [26,27]. This leads to the recruitment and activa- tion of the cytosolic tyrosine kinase Syk.…”
Section: The Kinase Activities Of the Src-family Kinases Fyn And Lyn mentioning
confidence: 99%
“…Importantly, the level of c-Cbl expression was similar in platelets de®cient in the two tyrosine kinases. These results could re¯ect an indirect role of Fyn and Lyn, which mediate tyrosine phosphorylation of the FcR g-chain [4], but could also re¯ect a direct contribution to c-Cbl tyrosine phosphorylation.…”
Section: Phosphorylation Of C-cbl In Murine Platelets Activated By Gpmentioning
confidence: 94%
“…The Src family kinases Fyn and Lyn play an early role in platelet activation by GPVI, upstream of the tyrosine kinase Syk and the effecter enzyme PLCγ2 (10)(11)(12). Roles for Src kinases in signaling downstream of other platelet receptors, including α2β1 (16) and GPIb-IX-V (26,32) have also recently been revealed.…”
Section: Src Kinase Inhibition Abolishes Platelet Aggregation and Parmentioning
confidence: 99%
“…The identification of the GPVI-Fc receptor (FcR) γ-chain complex as the principal receptor underlying activation by collagen (6)(7)(8)(9), and the elucidation of its Src kinase-dependent signaling cascade (10)(11)(12), provided the means to develop experimental tools to assess the two-site, twostep model. The availability of mouse platelets that are deficient in α2β1, GPVI, or FcR γ-chain was of particular importance in this regard, due to the small number of human patients that are deficient in these proteins.…”
mentioning
confidence: 99%